Motivasi Orangtua Nelayan Menyekolahkan Anaknya Sampai ke Perguruan Tinggi di Desa Segati Kecamatan Langgam Kabupaten Pelalawan - Sovia Sahara; Titi Maemunaty; Said Suhil Ahmad; Aswandi Bahar (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This article is intended to review how the motivation of fishermen's parents to send their children to college in Segati Village, Langgam District, Pelalawan Regency. The method of this article uses descriptive qualitative research, which is aimed at reviewing the problems that exist in the field and getting an essence that is in accordance with the circumstances in which the research was conducted, which uses a qualitative approach with the aim of measuring the interest of fishermen's parents in sending their children to college in the village. Segati Langgam District, Pelalawan Regency. The results of this research are intrinsic and extrinsic motivation, 1) Intrinsic motivation is a motivation that is attached to work situations that are purposeful and satisfy needs. Another name for this motivation is pure motivation, namely motivation that arises from within the individual to achieve goals, 2) extrinsic motivation comes from outside oneself. Intrinsic motivation includes: (1) Interests, (2) Attitudes, (3) Desire and extrinsic motivation include (1) Family, (2) School environment, (3) Community environment. The conclusion of this study In terms of intrinsic motivation that fishermen's parents have interests, attitudes and desires to send their children to tertiary institutions, namely the interest of fishermen's parents in sending their children to tertiary institutions by feeling interested. Because it can help the family's economy and not be underestimated by others and Judging from the extrinsic motivation that is support from the family, fishermen's parents send their children to college. With loving parents, parents pay attention by taking the time to tell stories with their children, parents never discriminate against their children. Keywords: Motivation, Parents, Fishermen